PERANCANGAN SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEB PADA BIMBINGAN BELAJAR SMART HOME - Adriana, Windy; Elzas, Elzas; Ibnu Ridwan, Ahmad; Windy Adriana (LP2M Universitas Nurdin Hamzah, 2024)
The advancement of information technology has brought major changes to all aspects of life, including in the field of education. Like in the Tutoring or Bimbel institution, in the Smart Home Tutoring they still use manual methods for registration and administration. The Smart Home Tutoring Institution in Jambi has difficulties because the registration process is still conventional, which means prospective students and parents must be present in person at the tutoring place. In certain situations, this step will be very difficult, especially for working parents. Therefore, a web-based information system is needed to facilitate the registration and administration process at the Smart Home Tutoring